Live Streaming Platforms and the Critical Discourse About Video Games - Felczak, Mateusz (Replay. The Polish Journal of Game Studies, 2017)
This work concerns online streaming platforms centered on broadcasting video games-related content, such as Twitch.tv and Douyu.com. The aim of this article is two-fold: first, to point out the possible research methods regarding online streaming services as mediums for video game criticism, and second, to assess the potential of these platforms for generating critical discourse about video games. The methodology of the research is based on Mia Consalvo’s take on paratextual frameworks and Veli-Matti Karhulahti’s notions of interview and play frames regarding the activity of video games streaming. In this article, the initial characterization of Twitch.tv and Douyu.com is followed by an analysis on how the work of streamers as content creators can influence the reception of video games. Afterwards, a reading of analyzed phenomena based on paratextual framework is proposed. The last section juxtaposes the initial findings with the perspective of changing viewership figures in relation to selected ludic properties of games. In conclusion, it is stated that the analyzed streaming platforms reflect the proliferating crowdsource trends in the video game industry, with forms of interacting with the product at various stages of its development cycle establishing new practices of talking in and about video games.